Targeting Novel Regulated Cell Death: Pyroptosis, Necroptosis, and Ferroptosis in Diabetic Retinopathy - Gao, Sheng; Zhang, Yun; Zhang, Meixia (Frontiers in Cell and Developmental Biology, 2022)
Diabetic retinopathy (DR) is one of the primary causes of visual impairment in the working-age population. Retinal cell death is recognized as a prominent feature in the pathological changes of DR. Several types of cell death occurrence have been confirmed in DR, which might be the underlying mechanisms of retinal cell loss. Regulated cell death (RCD) originates from too intense or prolonged perturbations of the intracellular or extracellular microenvironment for adaptative responses to cope with stress and restore cellular homeostasis. Pyroptosis, necroptosis, and ferroptosis represent the novel discovered RCD forms, which contribute to retinal cell death in the pathogenesis of DR. This evidence provides new therapeutic targets for DR. In this review, we summarize the mechanisms of three types of RCD and analyse recent advances on the association between novel RCD and DR, aiming to provide new insights into the underlying pathogenic mechanisms and propose a potential new strategy for DR therapy.